Longitudinal effect of a computer-based graduated prompting assessment on students' academic performance. (July 2017) - Zhang, Ren-Cheng; Lai, Hui-Min; Cheng, Po-Wen; Chen, Chin-Pin
Abstract: The dynamic assessment (DA) approach has been shown to be a useful evaluation tool for understanding students' learning potential. In the present learning context via technology-mediated learning (TML), the DA approach has a significant effect on learning. The aim of this study was to understand two gaps in the research on the effect of DA (in our case, computer-based graduated prompting assessment) on students' academic performance. First, the extant research has focused on DA that is based on pre- and post-test evaluation. The influence of time is an important predictor of information technology use, and understanding the effect of computer-based DA on students' academic performance across time is thus necessary. Second, the TML-based assessment has been designed because the assessment system has students who receive help directly in isolated TML environments. As such, we developed a TML-based, computer-based graduated prompting assessment and conducted a longitudinal examination of computer-based graduated prompting assessments in graphing courses. Quasi-experiments involving 60 students in an experimental group and 60 students in a control group were conducted to test the growth model of hierarchical linear modeling. The results showed that this assessment statistically significantly influenced students' academic performance, as might be expected. However, the use of this assessment over time did not lead to a change in the growth rate. Recommendations for using computer-based graduated prompting assessments across a long timeframe to prompt students' academic performance are also discussed. Highlights: A computer-based graduated prompting assessment was developed. The growth model of HLM was used to test the hypotheses. The use of assessment significant affected students' academic performance. The use of assessment over time did not show a change in the growth rate.